The Effect of Ict Innovations on Tax Compliance in Uganda - John Jonathan Musoke (Uganda Christian University, 2023)
This study set to examine effects of ICT innovations and tax compliance in Uganda. The study examined the effect of ICT innovations (electronic tax system) on tax compliance, established the challenges faced by the tax payers in using electronic tax system and suggested ways of improving the electronic tax system to enhance tax compliance. A descriptive survey design using a sample of 56 respondents was adopted. Simple random sampling and purposive sampling techniques were used to select the respondents and data was collected using well designed structured questionnaires and interview guide. Findings reveal that e-filing is easy for taxpayers which increases tax compliance as reflected by a mean value of 4.45. It was also established that tax payers are faced with a challenge of intermittent power supply and Internet outages and this is revealed by a mean of 3.63. It was also established that the use of automation of revenue collection system increases the revenue collection as shown by a mean value of 3.48. In conclusion, there is a direct relationship between internet payment system, electronic billing machine, mobile payment system and tax compliance. The study recommends that URA should adopt the use internet payment system to allow tax officers to issue assessments and refunds more quickly and lower corruption by reducing face-to-face interactions. URA should adopt the use mobile tax payment system so that clients can pay tax easily from anywhere by use of their mobile phone. In addition, EBM should be provided to different business enterprises across the country for easy accessible by customers, so that quick service and convenience is maintained hence increasing tax compliance.
This is a dissertation.